Occupation-Based treatment: Are We prepared. (2nd October 2019) - Colaianni, Donna; Harlowe, Amanda; Beyer, Samantha; Martir, Kaylee; Bennett, Mark; Dispoto, Laura; Johnson, Hillary; Kuhns, Ashton
Abstract: Aim : The purpose of this study is to determine the readiness of occupational therapy clinics to address the occupations their clients' may be interested in. Methods: A quantitative survey study of 59 geriatric occupational therapists who work in the state of Virginia examined the preparedness of the clinics they are employed in to address common client interests. Data was analyzed using SPSS version 25.0 software. Results: Practitioners reported their facilities are more prepared to address interests preferred by females than interests preferred by males and interests preferred by rural dwellers than interests preferred by non-rural dwellers. Conclusion: Preparedness to address patients' interests is lacking and varies depending on the patient's location of residence and gender.